2021
DOI: 10.1029/2020gl091595
|View full text |Cite
|
Sign up to set email alerts
|

The Statistical Morphology of Saturn’s Equatorial Energetic Neutral Atom Emission

Abstract: We present a definitive Cassini-era picture of Saturn's global energetic neutral atom morphology using remote sensing imagery.• Concentric tori of hydrogen and oxygen emissions are most intense at ∼ 7 − 10 Saturn radii in the equatorial plane, offset towards the dayside.• The intensity within 6−12 Saturn radii exhibits clear rotational modulation with north and south magnetic phase systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 74 publications
(132 reference statements)
1
10
0
Order By: Relevance
“…We observed that this creates an exponential tail toward low fluxes in the histograms, visible as a straight line in the log‐log scaled histograms in Figures 5c–5f and in good agreement with the real data shown in Kinrade, Bader, et al. (2020).…”
Section: Instrument Response and Effects Of The Projection On The Flu...supporting
confidence: 90%
See 3 more Smart Citations
“…We observed that this creates an exponential tail toward low fluxes in the histograms, visible as a straight line in the log‐log scaled histograms in Figures 5c–5f and in good agreement with the real data shown in Kinrade, Bader, et al. (2020).…”
Section: Instrument Response and Effects Of The Projection On The Flu...supporting
confidence: 90%
“…These may be caused by the periodic thinning and thickening of Saturn's equatorial plasma sheet by planetary period oscillation systems, two rotating systems for field‐aligned currents which originate near Saturn's poles and span its entire magnetosphere (e.g., Cowley & Provan, 2017; Jackman et al., 2016; Provan et al., 2018). This thickness modulation is also observed in the statistical ENA intensity (Kinrade, Bader, et al., 2020) and may trigger periodic reconnection in the magnetotail (e.g., Bader et al., 2019; Bradley et al., 2018, 2020).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Instead, they offer an independent validation of earlier findings, which indicated that the pointing of Saturn's inner convective electric field can be highly variable with L‐shell and time (Andriopoulou et al., 2013; Roussos et al., 2019). Recently, the mission‐averaged ENA image shows a similar radial offset toward the postnoon sector (Kinrade et al., 2021), validating the long‐term direction using an independent data set and measurement approach.…”
Section: Discussionmentioning
confidence: 63%